2010
DOI: 10.1159/000321370
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical, Radiographic and Laboratory Evaluation of Prognostic Factors in 363 Patients with Malignant Pleural Mesothelioma

Abstract: Background: Malignant pleural mesothelioma (MPM) has a poor prognosis. Objectives: Only few studies in literature investigated the presence of pleural fluid and radiographic findings for the prognosis of MPM. Methods: We retrospectively investigated the hospital charts of 363 MPM patients who were diagnosed from January 1989 to March 2010. Survival time was calculated by the Kaplan-Meier method. Pretreatment clinical, laboratory and radiographic features of each patient at the time of diagnosis were obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
1
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 64 publications
8
54
1
3
Order By: Relevance
“…10,11) Indeed, in patients with malignant pleural mesothelioma, it is reported that high WBC count and elevated CRP level associated with poor survival. 12,13) Also, in this patient, the tumor had a very rich blood supply and the prognosis was poor. Although G-CSF production from the mesothelioma cells was not apparent and the levels of other inflammatory cytokines were not measured, an immune response in the area might have contributed to progression of the malignancy.…”
Section: Discussionmentioning
confidence: 78%
“…10,11) Indeed, in patients with malignant pleural mesothelioma, it is reported that high WBC count and elevated CRP level associated with poor survival. 12,13) Also, in this patient, the tumor had a very rich blood supply and the prognosis was poor. Although G-CSF production from the mesothelioma cells was not apparent and the levels of other inflammatory cytokines were not measured, an immune response in the area might have contributed to progression of the malignancy.…”
Section: Discussionmentioning
confidence: 78%
“…With respect to MM, two retrospective screening studies suggested CRP as potent prognostic marker. High levels of serum CRP have been associated with poor prognosis due to the role of chronic inflammation in the development of MM that has been well established (Tanrikulu et al, 2010;Nojiri et al, 2011). A major limitation of all of the staging systems is the difficulty in assessing the extent of disease prior to treatment.…”
Section: Figure 2 Multivariate Analysis Results For Advanced Stage Smentioning
confidence: 99%
“…5 LDH level was determined in serum using heparin and citrate and an autoanalszer, (Architect 1600c, Abbott Laboratories, Irving, TX, USA). LDH level was measured in tubes with K2 ethylenediaminetetra-acetic acid.…”
Section: Potential Prognostic Parametersmentioning
confidence: 99%